Adoption of Artificial Intelligence in News Gathering and Reporting in Nigerian Mass Media - TALABI, Felix Olajide; OYEWOLE, John Ayodele; BELLO, Samson Adedapo; ADEFEMI, Victor Oluwole; TALABI, Joseph Moyinoluwa; ADESILE, Tosin; OLADELE, Patrick Olajide (Journal of Ecohumanism, 2024)
This study looks at how artificial intelligence (AI) is employed in news reporting and gathering in Nigerian mainstream media, with a focus on LTV and TVC. The study’s goals are to find out how much AI is employed in these TV stations, as well as what the benefits and challenges are of doing so, and what the ethical implications are of incorporating AI into journalism. The study conducted in-depth interviews with journalists from LTV and TVC to gain information on their viewpoints and experiences about the usage of AI in their news gathering and reporting methods. The findings demonstrate the growing use of artificial intelligence (AI) in data analysis, automation, and content creation for news reporting. Nonetheless, the research also emphasizes the difficulties and moral dilemmas that come with the use of AI, such as the possibility of prejudice, the loss of jobs, and the requirement for accountability and transparency. According to the study’s findings, artificial intelligence (AI) has the potential to completely transform Nigerian journalism. Still, its implementation would need to be carefully regulated to get the best results for society and the media.